A Comparative Cross-Sectional Study on the Prevalence of Impostor Phenomenon in Medical and Non-Medical Students of Lahore City - Lareib Raashed; Afia Liaqat; Maheen Nasir; Maheen Tariq; Zainab Omer (University Library System, University of Pittsburgh, 2023)
BACKGROUND: The Imposter Phenomenon (IP) is a psychological pattern emphasizing feelings of uncertainty and inadequacy despite evidence and acknowledgement of one's competence and accomplishments. It is commonly found among excelling individuals who believe that they have somehow "tricked" others into thinking that they are more capable than they are. There are over 1200 published researches on Impostor Phenomenon since 1978 and this has led to the development of various measurement scales but the Clance Impostor Phenomenon Scale is the most commonly used instrument by researchers. Till now, there have been various researches regarding the prevalence of the IP among students but there has yet to be a study on a comparison between medical and non-medical students. AIM: The aim of this study is to compare the prevalence and distribution of Imposter phenomenon among medical and non-medical students, as well as to compare the difference in its distribution between males and females. METHODS: A cross-sectional comparative research design was used on a sample of 242 medical and non-medical students of CMH Lahore Medical and Dental College and Lahore University of Management Sciences (LUMS), respectively. The inclusion criteria were medical and non-medical students of both universities while the exclusion criteria were students, who refused to give consent. Data was collected from January to April 2023 and all participants completed a questionnaire based on the Clance Impostor Phenomenon (CIP) scale. After the collection of the data, it was assessed using SPSS version-26 and the the Clance Impostor Phenomenon score was calculated. The CIP score is organized into 4 sets and suggests the range of Impostor Phenomenon (IP) characteristics: <=40 total score (Mild IP), 41-60 total score (Moderate IP) 61-80 total score (Frequent IP characteristics), >=81 total score (Severe IP) RESULTS: After analyzing, using unpaired T-test on the data, the study showed both medical and non-medical students experience imposter phenomenon to a certain degree but the prevalence of imposter phenomenon was found to be significantly higher among LUMS (non-medical) students as compared to CMH (medical) students. The total CIP score determined the severity of IP and showed LUMS having a higher mean value of 67.08 (±13.704), and CMH having 58.36 (±11.413) suggesting much more frequent IP characteristics in non-medical students. It was also noted that although the Imposter phenomenon is observed in both genders, it is much more significant in females with a mean of 68.39 (± 13.737) and 58.52 (±11.345) for males, again showing females to experience frequent impostor phenomenon characteristics. CONCLUSION: In conclusion, this study provides evidence that imposter phenomenon is prevalent among both medical and non-medical students and it highlights the need for educators and mentors to focus on the prevailing issue so that this phenomenon can be countered for their future professional growth. To break the vicious cycle of negativity, effort needs to be put in by both students and teachers to be able to achieve positive results.